DRIVER PREFERENCE CONCERNING IN-CAR ROUTE GUIDANCE AND NAVIGATION SYSTEM MAPS FOR DRIVERS WITH COLOR VISION DEFICIENCY - Renan Furlan de Oliveira (Boletim de Ciências Geodésicas, 2018)
In-car Route Guidance and Navigation Systems (RGNS) are used to help drivers navigate. These maps have mainly been designed to accommodate drivers with normal color vision. However, the color perception of people with normal color vision differs from that of people with color vision deficiency. When navigating, understanding certain kinds of information presented by RGNS maps can be a more complex task for colorblind drivers and traffic safety may be impacted negatively. An important aspect related to the graphic design of RGNS maps is the use of a good combination of colors to improve map legibility. Cartographic representations with good legibility aid drivers in comprehending information and making appropriate decisions during driving tasks. This paper evaluates driver preference for RGNS maps designed for drivers with color vision deficiency. A total of 14 subjects participated in an experiment performed in a parked car. Maps were designed to accommodate red-blinds and green-blinds by using a color simulator and principles of perceptual grouping and figure-ground segregation. Based on the results, we conclude that the map grouping symbols representing car and direction arrows in blue segregated from the route in black was more acceptable to drivers compared to other combinations. It is recommended that RGNS should offer a specific graphic design to support drivers with color vision deficiency in navigating.